Evaluation of two remediation techniques applied to a site impacted by petroleum production waters - Gómez-Mellado, Ambar Yuridia; Morales-Bautista, Carlos Mario; De la Garza-Rodríguez, Iliana Margarita; Torres-Sánchez, Sonia Alejandra; Sánchez-Lombardo, Irma (REVISTA TERRA LATINOAMERICANA, 2020)
Salinity in soils is a problem that has increased in recent years, in the Mexican southeast one of the main sources associated with these effects is the oil production water, affected congenital water. Although the chemical composition changes between one site and another, it is documented that its components can cause harmful effects on health and ecosystems. To recover the vocation to use recovery areas, different treatments have been established that eliminate standardized parameters, but others that may influence soil quality are not considered. Therefore, two treatment techniques of a soil contaminated experimentally with congenital waters were evaluated, these were; cation exchange and natural attenuation, the evaluation consists in comparing the physical and chemical properties of the control soil, treated and treated after one year, some heavy metals are also determined in all of them. In the results, it is modif ied that the pollutant causes changes in the soil, such as, pH reduction (neutral to acid), porosity (20%), f ield capacity (50%) and organic matter (50%), as well as an increase in salinity (without saline to saline) and densities (10%), it is also increased that the concentrations of Pb, Zn, Ni increase. Na, Fe and V and Ca and K were reduced. Both treatments reduce salinity, but natural attenuation shows better results than cation exchange, mainly in pH, f ield capacity and textures, but with higher concentrations of sodium with respect to the witness in both cases, the metals are below the regulatory limit before and after the treatment, but when compared with control soils a level of increase in V and Pb is noted, because the area is immersed in oil activities, it is advisable to carry out long-term bioaccumulation studies.